Distinct Phenotypes Caused by Mutation of MSH2 in Trypanosome Insect and Mammalian Life Cycle Forms Are Associated with Parasite Adaptation to Oxidative Stress. - Viviane Grazielle-Silva; Tehseen Fatima Zeb; Jason Bolderson; Priscila C Campos; Julia B Miranda; Ceres L Alves; Carlos R Machado; Richard McCulloch; Santuza M R Teixeira (PLoS Neglected Tropical Diseases)
Background DNA repair mechanisms are crucial for maintenance of the genome in all organisms, including parasites where successful infection is dependent both on genomic stability and sequence variation. MSH2 is an early acting, central component of the Mismatch Repair (MMR) pathway, which is responsible for the recognition and correction of base mismatches that occur during DNA replication and recombination. In addition, recent evidence suggests that MSH2 might also play an important, but poorly understood, role in responding to oxidative damage in both African and American trypanosomes. Methodology/principal findings To investigate the involvement of MMR in the oxidative stress response, null mutants of MSH2 were generated in Trypanosoma brucei procyclic forms and in Trypanosoma cruzi epimastigote forms. Unexpectedly, the MSH2 null mutants showed increased resistance to H2O2 exposure when compared with wild type cells, a phenotype distinct from the previously observed increased sensitivity of T. brucei bloodstream forms MSH2 mutants. Complementation studies indicated that the increased oxidative resistance of procyclic T. brucei was due to adaptation to MSH2 loss. In both parasites, loss of MSH2 was shown to result in increased tolerance to alkylation by MNNG and increased accumulation of 8-oxo-guanine in the nuclear and mitochondrial genomes, indicating impaired MMR. In T. cruzi, loss of MSH2 also increases the parasite capacity to survive within host macrophages. Conclusions/significance Taken together, these results indicate MSH2 displays conserved, dual roles in MMR and in the response to oxidative stress. Loss of the latter function results in life cycle dependent differences in phenotypic outcomes in T. brucei MSH2 mutants, most likely because of the greater burden of oxidative stress in the insect stage of the parasite.